The Role of Employee Engagement in Mediating the Effect of Perceived Organizational Support on Employee Performance (A Study of F&B Department Employees at Puri Santrian A Beach Resort and Spa Sanur) - Komang Sri Mediani Dewi; Agoes Ganesha Rahyuda (Indonesian Journal of Business Analytics, 2026)
Employee performance is an essential factor determining a company’s success in achieving its organizational goals. One important factor that can affect how well employees perform is the level of perceived organizational support. Employees tend to thrive when they feel that their company fosters a supportive work setting, making them feel valued and recognized. This study seeks to explore how organizational support impacts employee performance, particularly by looking at employee engagement as a mediating variable. The research involved employees from the F&B department at Puri Santrian A Beach Resort and Spa Sanur, and it included 54 respondents who were chosen using the census method. Data were gathered using an online survey sent out through Google Form. For analyzing this data, the study utilized path analysis with the help of SPSS version 22.0. The findings show that organizational support positively and significantly impacts employee performance. Additionally, organizational support also positively affects employee engagement in a significant way. Moreover, employee engagement is shown to positively and significantly influence employee performance. It has been set up that worker engagement mostly intercedes the relationship between organizational back and representative execution. This research enhances the understanding of Social Exchange Theory and aims to provide companies with insights to improve organizational support, ultimately boosting employee engagement and performance in the workplace.